Efecto de la edad y la temperatura del escaldadoen la terneza del cuy (Cavia porcellus) - Gutiérrez Plasencia, Gissela Janeth (2012)
The aim of this research was to evaluate the effect of the age of the guinea pig and the temperature of scalding in its tenderness. In this study, three, six and nine month old “Peru line” guinea pigs from farms in Trujillo were scalded at 65, 75 and 85 °C in a time of 15 seconds. Factorial Experimental 3x3 design was used, with three repetitions. The sensorial evaluation was carried out by a 10 person trained panel using a Non Structured Scale. This evaluation was done with three repetitions. SPSS 15 Computer Statistical Program was used for processing the ANVA which showed significant differences, in the treatments. Was carried outthen DUNCAN Multiple Comparisons obtaining as result that the best treatment was “T1” (3 months, 65ºC).